Recurrent Ureteral Obstruction Revealing Malignant Lymphoma in a Young Adult : A Case Report - Faathira Amalika Dewinadira Yusna; Abdul Malik Yusuf (International Medical Journal Corp. Ltd, 2026)
Introduction Extranodal presentations of malignant lymphoma represent a significant diagnostic challenge for clinicians, as they frequently mimic more common organ-specific pathologies. While the lymphatic system is the primary origin of these neoplasms, approximately 25% to 40% of Non-Hodgkin Lymphoma (NHL) cases originate in extranodal sites.1 Genitourinary (GU) tract involvement is particularly rare, accounting for less than 5% of all primary extranodal lymphomas.4 Among GU involvements, prostatic and ureteral infiltrations are exceedingly uncommon, often manifesting as non-specific lower urinary tract symptoms (LUTS) or acute renal failure due to obstructive uropathy.6 In young adults, the diagnosis of malignant ureteral obstruction (MUO) is often delayed because medical attention initially focuses on metabolic urolithiasis or congenital anatomical anomalies.9 Case Illustration A 27-year-old male presented with a history of a neck tumor excision in 2022, which initially suggested Hodgkin Lymphoma (HL) or a Giant Cell Soft Tissue Tumor. Due to the patient’s refusal of systemic chemotherapy, the disease progressed over three years. In June 2025, he presented with acute-on-chronic kidney injury (AKI/CKD) and bilateral hydronephrosis. Endoscopic evaluation through ureterorenoscopy (URS) revealed no lithiasis but identified significant bilateral ureteral stiffness and strictures. Despite temporary stabilization with double-J (DJ) stents, the patient experienced recurrent obstruction within two months. Subsequent transurethral resection of the prostate (TURP) and ureteral evaluation revealed widespread mural infiltration. Histopathology and immunohistochemistry (IHC) confirmed a malignant tumor suggestive of lymphoma, with leukocyte common antigen (LCA) and CD20 positivity. Further staging identified systemic lymphadenopathy, chylothorax, and sclerotic/lytic spinal metastases at the C1, C4, and TH3 levels. The patient eventually succumbed to complications of uremic encephalopathy and disseminated disease. Discussion The diagnostic hallmark of this case was the